How effective is a group based motivational interviewing intervention in promoting pupil resilience and self-esteem? - Moss, Claudia (2010)
The research examined the impact of a five week group-based motivational interviewing intervention on pupils’ self-esteem and resilience. The Resiliency Scales for Children and Adolescents (Prince-Embury 2007) and The Self Image Profiles (Butler 2001) were used as tools to obtain pre and post measures of pupil resilience and self-esteem. The researcher also explored teacher and pupil views of mental well being and Goodman’s (1997) Strengths and Difficulties Questionnaire was utilised to measure this.